Substantive evidence of initial habitation in the remote Pacific : archaeological discoveries at Unai Bapot in Saipan, Mariana Islands /: archaeological discoveries at Unai Bapot in Saipan, Mariana Islands. (2017) - Carson, Mike T; Hong, Xiaojun
No abstract available